Study Of Architectural Motifs Used In Aitchison College’s Main Building - Humera Omer Farooq (Al-Qanṭara, 2022)
Lahore is the city which carries the architectural aromas of many races, dynasties and cultures. Aitchison’s College building is one of those masterpieces that depict the amalgamation of the past and contemporary influences. Its buildings speak the story of the people once lived and governed this very piece of land. Architects and artisans are among those privileged artist whose work becomes the element of recognition of a certain place. The patterns and motifs used in an artwork is the link that attaches and all kind of artworks of a certain time and era may it be paintings, sculpture or an architectural building. These motifs also show artists affiliation or influence towards a certain religion or time or theory as many motifs are associated with different cultures and religions as well. The study of the motifs used in Aitchison’s Old building helps us find the sources and influences that dominated the architects behind this masterpiece.